Market competition in the downstream oil industry is there evidence of price asymmetry? - Abrenica, Ma. Joy; Danao, Rolando A.; Mendoza, Nimfa Ma. (2014)
Casual observation that domestic gasoline prices increase immediately and more than proportionately when global prices rise, while they tend to decrease slowly and less than proportionately when global prices decline, has fuelled speculation that the major oil industry players are engaging in collusion. This perception has persisted despite three independent probes into the state of market competition in the industry—none of which found direct evidence of collusion. However, the third inquiry has found some evidence of price asymmetry in a recent period. Applying a standard price asymmetry model with error correction term on weekly price data, this study finds no evidence of price asymmetry. Instead, local pump prices are confirmed to be tracking global prices symmetrically and with only a week’s lag. This finding is robust for different fuel types.
Keywords: Price fixing; Competition in the petroleum industry